AL-QUR’AN DAN AL-SUNNAH SEBAGAI DASAR IDEAL PENDIDIKAN ISLAM - Akmansyah, Muhammad (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2015)
Education in the context of Islam is regarded as aprocess that involves the complete person, including therational, spiritual, and social dimensions, all entwined inunified perceptual framework and relying, entirely, in itsfundamentals and morals on the Holy Quran and theProphet‟s Sunnah. Through Islamic education,individuals are educated and cultured following an allencompassing method that involves all aspectsmentioned, without compromising any, or giving primacyof one over the other. So, Islamic education is uniquelydifferent from other types of educational theory andpractice largely because of the all-encompassing influenceof the Holy Quran and the Prophet‟s Sunnah. Bothserves as a comprehensive blueprint for both theindividual and society and as the primary source ofknowledge.